Study of machines performance in producing different sizes of grated sago - Wan Azman, Wan Mohd Fariz; Shamsudin, Rosnah; Hamzah, Azman; Azizan, Mohd Shahrir; Azizan, Saiful Azwan; Shahar, Asnawi; Rahim, Afiqah Aina; Mhd Adnan, Amir Syariffuddeen; Hasbullah, Hasmin Hakim; Hashim, Ishak; Sairi, Masniza; Abdul Wahid, Ruwaida; et al. (Penerbit MARDI, 2018)
Sago starch is a product from sago palm. In order to extract the sago starch, certain process is needed to break the bonding of the pith either mechanically or manually by grating the pith into small sizes. Water is widely used as a solvent medium in the extraction process of sago starch. The more refined that grated sago, the more sago starch can be dissolved from the grated sago. Different machines were used to produce grated sago for machine capability test. The machines are handheld chainsaw, coconut husk decorticator, commercial coconut grater and in-house roller grating prototype. Sago palm trunk was cut into three parts with length of 50 cm long each. The outer layer of each sago palm trunks was peeled off and split into 8 pieces. All sago trunks were grated using four different machines as stated above. Each 100 gram of the grated sago trunk produced by each machine were sifted according to the grading size of 2.80 mm, 2.00 mm, 1.00 mm, 0.85 mm and 0.425 mm. The weights of sago starch from the sieving process were recorded according to their respected grading size. Based on results of the sieve experiments, the most finest grated sago trunk was produced from the handheld chainsaw with a weight percentage ratio of 13.028% (X < 0.3 mm), 10.682% (0.3 ≤ X < 0.425 mm), 28.361% (0.425 ≤ X <0.85 mm), 28.821% (0.85 ≤ X <1.0 mm), 4.728% (1.0 ≤ X <2.0 mm), 7.877% (2.0 ≤ X <2.8 mm), and 4.868% (X ≥2.8 mm) where X value refer to sieve mesh size.